Striatal BOLD response reflects the impact of herd information on financial decisions - Burke, Christopher J.; Tobler, Philippe N.; Schultz, Wolfram; Baddeley, Michelle (Frontiers in Human Neuroscience, 2010)
Like other species, humans are sensitive to the decisions and actions of conspecifics, which can lead to herd behavior and undesirable outcomes such as stock market bubbles and bank runs. However, how the brain processes this socially derived influence is only poorly understood. Using functional magnetic resonance imaging (fMRI), we scanned participants as they made decisions on whether to buy stocks after observing others’ buying decisions. We demonstrate that activity in the ventral striatum, an area heavily implicated in reward processing, tracked the degree of influence on participants’ decisions arising from the observation of other peoples’ decisions. The signal did not track non-human, non-social control decisions. These findings lend weight to the notion that the ventral striatum is involved in the processing of complex social aspects of decision making and identify a possible neural basis for herd behavior.